Impulsive Buying Behavior: Implementation of IT on Technology Acceptance Model on E-Commerce Purchase Decisions - Faradiva Dwi Azizah; A. Nirwana Nur; Aditya Halim Perdana Kusuma Putra (Manunggal Halim Jaya, 2022)
This study aims to determine the impact of implementing the Information System Technology Acceptance Model in supporting the tendency to use applications and impulse buying behavior on purchase decisions Shopee E-Commerce. This research approach uses quantitative research. The primary data sources used in this study are preliminary data obtained from questionnaires and secondary data. This research was conducted in the city of Makassar. The population in this study was drawn from the infinite population, with a sample of 315 respondent who were students in Makassar City. Data analysis used the validity test, reliability test, R-square test, F-square test, direct effect test, and partial least square (PLS) hypothesis submission. The results of this study indicate that the Technology Acceptance Model variable has a positive and significant effect on the Purchase Decision variable. Likewise, the impulsive buying behavior variable has a positive and significant effect on the purchase decision variable. The relationship between these variables is included in the dominant category of class I. Then the influence of the TAM on impulsive buying behavior is included in the predominant type of class II. This study's theoretical and managerial implications explain that the TAM and impulsive buying behavior can improve purchase decisions.